THE EFFECT OF MEMBER EMPOWERMENT PROGRAM ON THE WELFARE OF THE CREDIT UNION MEMBERS IN EAST JAVA - Nekhasius Agus Sunarjanto; Cicilia Erna Susilawati; Elisabeth Supriharyanti (KINERJA, 2020)
This study focuses on the institutions in the form of credit unions that provide credit loans to micro-businesses. The sample of this study consisted of 102 members of 15 different credit co-operatives in East Java as the research participants. The research objective of this study was to determine the effect of empowerment programs on the welfare of the members. The empowerment programs were divided into (1) educational, (2) training, (3) savings and loan, and (4) network development programs. The results showed that the empowerment programs through education and training programs had a significantly positive effect on increasing the welfare of the members, while the savings and loan programs as well as the network building program did not significantly affect the welfare of the members. This was possible because members who already had networks and received funding assistance would not succeed without good education and training programs. The research was expected to contribute academically in the development of savings and loan co-operative unions (CUs) and provide a foundation and solution for all CU administrators in developing the CUs, especially in improving the welfare of their members.Keywords: Credit Union, member empowerment, and member welfare